Integration of using Fintech and social media for the Sustainability Halal Business in Pesantren - Syamsu, Nur; Sofyan, Syaakir; Aisya, Sitti; MD, Muthmainnah (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2023)
The urgency of Fintech and social media in halal business to realize Halal Value Chain (HVC) That support the addition of economic value for halal businesses including business activities at Islamic boarding schools in the Society 5.0 era. The purpose of this study is to analyze the optimization of the integration of the use of financial technology and social media in halal businesses managed by Islamic boarding schools to achieve the SDGs in the 5.0 era. This study uses phenomenology with data sources from Islamic boarding schools in Central Sulawesi. This study uses phenomenology with data sources from Islamic boarding schools in Central Sulawesi. The results of the study indicate the optimization of the integration of the use of fintech and social media in halal business activities in the form of recording transactions, analysis of financial reports, decision making, market mapping, product innovation, resilience, and building and maintaining business networks.